Stromal and epithelial cells react differentially to c-kit in fibroepithelial tumors of the breast - Logullo, Angela F. [UNIFESP] (2008)
The CD117 protein is a tyrosine-kinase receptor encoded by the c-kit gene that frequently bears activating mutations in gastrointestinal tumors. Conflicting findings regarding CD117 expression in other stromal tumors, including phyllodes tumors (PTs), have been reported in the literature. the purpose of this study was to evaluate c-kit expression in the stroma and epithelia of fibroepithelial breast tumors and its correlation with clinical pathological variables. Ninety-six fibroepithelial tumors of the breast, including 14 fibroadenomas (FAs), 12 juvenile FAs and 70 PTs, were classified according to stromal cellularity, atypia, epithelial hyperplasia, mitosis and borders into 45 benign (PTB), 17 borderline (PTBL) and 8 malignant (PTM) tumors. CD117 expression was identified in the stromal component in only two cases of PTBL. Overall, 38 cases (39.6%) showed positive CD117 in the epithelial component, including 20 FAs (10 regular, 10 juvenile) and 18 PTs (11 PTBs and 8 PTBLs). Other cases, including all PTMs, 6 FAs (4 regular, 2 juvenile), 34 PTBs and 10 PTBLs, showed no positivity in the epithelial component. Expression of c-kit did not correlate with diagnosis or malignancy (p>0.05). in conclusion, c-kit is expressed more often in the epithelial than in the stromal component in fibroepithelial tumors of the breast, and is associated with benign lesions.